Biochemical studies of cocoa bean polyphenol oxidase - Pat, M Lee; Kong, Hung Lee; Abdul Karim, Mohd Ismail (John Wiley & Sons, 1991)
Polyphenol oxidase (EC 1.14.18.1) was isolated and partially purified from cocoa beans. The properties of the enzyme were studied. The Michaelis constant Km for catechol was 1 × 10−2 M. The pH optimum of polyphenol oxidase activity assayed with catechol as substrate occurred at pH 6.8 and was characterised by a relatively high thermal stability, 50% of its activity was lost after heating for 40, 25 and 5 min at 60, 69 and 80°C respectively. The optimum temperature for the enzyme activity with catechol as substrate was around 45°C. The enzyme was reactive towards 3‐(3,4‐dihydroxy phenyl)‐DL‐alanine, 3‐hydroxytyramine hydrochloride and 4‐methyl catechol but showed no activity towards tyrosine, p‐cresol, and 4‐hydroxy‐phenol. A rapid deactivation of the enzyme was observed when catechol of concentration > 40 mM was used as substrate. The enzyme activity was inhibited by ascorbic acid, L‐cysteine, sodium bisulphite and thiourea.